Application of Zakat Accounting Based on PSAK 109 in The Amil Zakat Agency Ternate City - Irman Mamulati; Marwia Abdullah; Wirawati Abdjan (Journal of International Conference Proceedings (JICP), 2020)
This study aims to analyze the application of zakat accounting based on PSAK 109 at the Amil Zakat Agency of Ternate City. The method used is descriptive comparative. The results showed that: (1) The accounting process at the Amil Zakat Ternate Agency in City was not fully in accordance with general accounting theory; (2) Recognition and measurement of zakat on Amil Zakat Ternate Agency was in accordance with PSAK 109; (3) Recognition and measurement of infaq/alms giving on Amil Zakat Ternate Agency was not fully in accordance with PSAK 109; and (4) Presentation and disclosure on Amil Zakat Ternate Agency was not in accordance with PSAK 109.